PEDAGOGICAL TECHNOLOGIES FOR DEVELOPING MORAL EDUCATION THROUGH EXTRACURRICULAR CREATIVE CLUBS - Turaxodjayeva Zulxumor Yusufjanovna (International Scientific and Current Research Conferences, 2025)
This article presents a comparative, regionally nuanced examination of Uzbek–Russian bilingualism across three sociohistorically distinct regions of Uzbekistan: Tashkent, the Fergana Valley, and Karakalpakstan. The study builds on sociolinguistic typologies of bilingualism and regional evidence from previous research to propose a model that links bilingual profiles to urbanization, institutional language regimes, educational and labor-market incentives, ethnolinguistic composition, and the interactional norms of everyday communication. The analysis indicates that Tashkent favors more stable and functionally diverse Uzbek–Russian bilingual repertoires, whereas the Fergana Valley predominantly displays Uzbek-dominant bilingualism, with Russian concentrated in particular institutional and mobility-related contexts. In Karakalpakstan, multilingual configurations and educational mediation influence Uzbek–Russian bilingualism in distinct manners, with Russian operating alongside Karakalpak and Uzbek in domain-specific contexts. The results are examined concerning language selection, code-switching, identity positioning, and the ramifications for educational and public communication policies.